Efektivitas Layanan Konseling Kelompok Teknik Positive Reinforcement untuk Meningkatkan Rasa Percaya Diri Siswa - Oktaviani Linggar Sari (Jurnal Bimbingan dan Konseling Terapan, 2022)
This study aims to determine the effectiveness of the Positive Reinforcement Technique group counseling technique to increase the self-confidence of class X students. The type of research used is experimental research with a one-group pretest-posttest design. The sample used in this study were 6 students from class X DKV SMK Negeri 2 Sewon who were identified as having low self-esteem. Data collection techniques using a questionnaire. The results of the study can be concluded that group counseling services with positive reinforcement techniques can increase self-confidence. This is shown from the results of the t-test obtained that there is a significant difference between the pretest score and the posttest score about self-confidence. This is shown t arithmetic = -18.602 sig 0.000 <0.0. Thus it can be concluded that there is an increase in student self-confidence after being given treatment in the form of positive reinforcement technique group counseling services. So this shows that Ha is accepted.